(untitled) (Global Journal of Human-Social Science, 2015)
This paper is concerned with the influence of the Anglican Church of Kenya (ACK) on poverty alleviation in Maseno and Winam Divisions of Kisumu District. It analyses some of the development activities the ACK is involved in as an attempt to improve the local people’s standard of living. Poverty is an outrage against humanity. It robes people of their dignity, power and hope of freedom and power over their own lives. This paper seeks to affirm that the Christian Churches in their teachings believe and insist that the world can be changed to one where everyone can live a full life, free from poverty. Similarly, the paper argues that any work for profound change that eradicates causes of poverty, striving to achieve equality, dignity and freedom for all regardless of faith or nationality is an indelible work of the Christian Church as amplified in the life and teachings of Jesus Christ. The paper concludes that the ACK has made some progress in its efforts to alleviate poverty and at the same time faced several challenges in Maseno and Winam Divisions.